2002
DOI: 10.1002/jbm.10031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium phosphate coating crystallinity and implant surface roughness on differentiation of rat bone marrow cells

Abstract: In this study, we examined the effect of calcium phosphate (Ca-P) coating crystallinity and of surface roughness on growth and differentiation of osteogenic cells. Grit-blasted titanium substrates were provided with Ca-P coatings of different crystallinities. Rat bone marrow (RBM) cells were cultured on these substrates and on noncoated rough and smooth titanium substrates. After specific culture times, expression of osteogenic markers by the cells was studied. Cells cultured on crystalline coatings and on tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 43 publications
7
49
3
Order By: Relevance
“…This corroborates with previous in vitro studies of our group in which the application of a CaP coating on solid Ti discs has been shown to delay the proliferation of rat bone marrow cells by 8 days, while differentiation was stimulated by 16 days. 36,38 This positive effect of a CaP coating can be mediated by an increased level of Ca 2+ ions that results from the superficial dissolution of the coating. Osteoblast-like cells have been shown to possess calcium receptors on their surface.…”
Section: Discussionmentioning
confidence: 99%
“…This corroborates with previous in vitro studies of our group in which the application of a CaP coating on solid Ti discs has been shown to delay the proliferation of rat bone marrow cells by 8 days, while differentiation was stimulated by 16 days. 36,38 This positive effect of a CaP coating can be mediated by an increased level of Ca 2+ ions that results from the superficial dissolution of the coating. Osteoblast-like cells have been shown to possess calcium receptors on their surface.…”
Section: Discussionmentioning
confidence: 99%
“…19 Additionally, they require special laboratory conditions, and they sometimes demand special conditions including contaminant-free working areas and are usually restricted to conductive materials. 20,21 As far as zirconia is concerned, electrical techniques are precluded, and acid or alkaline-etching techniques do not give rise to high-surface roughness levels, because the original material is manufactured using high-isostatic pressure to make it resistant to chemical, physical, or wear changes 22 . The reason for these geometric, physical, or chemical modification techniques is to enhance surface-cell interactions and to stimulate cellular activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of chemical methods modify not only topography, but also other surface features such as chemical composition, [25] wettability, [26] crystallinity, [27] and adsorption ability. [28] These surface observables can also modulate cell behavior [27,[29][30][31] (for more information about surface modification strategies and cellular recognition of these surfaces see the review papers [32,33] ) and it is difficult to distinguish which factor leads to the observed cell response.…”
Section: Introductionmentioning
confidence: 99%